Organizing pneumonia as a possible pulmonary manifestation of systemic lupus erythematosus: Three cases and a review of literature. (May 2022) - Ito, Yuhei; Tamada, Tatsuya; Okunishi, Yuki; Mizutani, Satoshi; Yamamoto, Yoshiki; Nakajima, Ayako
Background: Organizing pneumonia (OP) is a rare manifestation of systemic lupus erythematosus (SLE). It has been described in very few case reports. Purpose and Methods: We encountered OP in three patients with SLE in 1 year; two manifested OP as an initial presentation of SLE, while the third manifested OP when SLE relapsed. To elucidate the clinical features and outcomes of OP in patients with SLE, we screened the PubMed database for cases diagnosed with OP either at or after the diagnosis of SLE; the search was restricted to articles that were published after 1990, when OP became widely recognized. Results: We identified 15 cases of OP in patients with SLE. Thus, we analyzed a total of 18 cases (including our three). OP developed at the initial diagnosis of SLE in 15 cases and at relapse of SLE in three cases. In most cases, the disease activity of SLE was moderate or high. In all cases, OP was accompanied by other extrapulmonary symptoms of SLE, namely, fever (77.8%), cutaneous manifestations (61.1%), arthralgia/arthritis (50%), and lupus nephritis (33.3%). Steroid monotherapy or increasing the dose of the steroids was effective in seven cases (38.8%); however, steroid monotherapy was ineffective and led to death due to respiratory failure in two cases (11.1%). Combination therapies of steroids with hydroxychloroquine, azathioprine, tacrolimus, mycophenolate mofetil, intravenous pulse cyclophosphamide therapy, and belimumab were effective in seven cases (38.8%). Conclusions: Based on the review of previously reported and our cases, we concluded that OP is an important pulmonary manifestation of SLE. Clinicians should be aware of it as it may require intensive immunosuppressive therapy either at or after the diagnosis of SLE.